A plastid-targeted heat shock cognate 70-kDa protein confers osmotic stress tolerance by enhancing ROS scavenging capability - Ding, Feng; Li, Fan; Zhang, Binglei (Frontiers in Plant Science, 2022)
Osmotic stress severely affects plant growth and development, resulting in massive loss of crop quality and quantity worldwide. The 70 kDa heat shock proteins (HSP70s) are highly conserved molecular chaperones that play essential roles in cellular processes including abiotic stress responses. However, whether and how plastid-targeted heat shock cognate 70 kDa protein (cpHSC70-1) participates in plant osmotic stress response remain elusive. Here, we report that the expression of cpHSC70-1 is significantly induced upon osmotic stress treatment. Phenotypic analyses reveal that the plants with cpHSC70-1 deficiency are sensitive to osmotic stress and the plants overexpressing cpHSC70-1 exhibit enhanced tolerance to osmotic stress. Consistently, the expression of the stress-responsive genes is lower in cphsc70-1 mutant but higher in 35S:: cpHSC70-1 lines than that in wild-type plants when challenged with osmotic stress. Further, the cphsc70-1 plants have less APX and SOD activity, and thus more ROS accumulation than the wild type when treated with mannitol, but the opposite is observed in the overexpression lines. Overall, our data reveal that cpHSC70-1 is induced and functions positively in plant response to osmotic stress by promoting the expression of the stress-responsive genes and reducing ROS accumulation.